1984
DOI: 10.1002/ajmg.1320170414
|View full text |Cite
|
Sign up to set email alerts
|

The Bartsocas‐Papas syndrome: Autosomal recessive form of popliteal pterygium syndrome in a male infant

Abstract: We report on an additional patient with the severe autosomal recessive form of the popliteal pterygium syndrome. The patient was diagnosed at birth and had all of the phenotypic manifestations of this rare syndrome. Clinical findings and natural history suggest this is a distinct genetic entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Mental retardation was a part of this variant and very few of the patients survived the first few weeks of life. 13 Our patient was three months of age and her postnatal mental and physical growth and development were normal. It was reported to be a sporadic case by the genetics department as there was no genetic abnormalities in her parents and relatives.…”
Section: Discussionmentioning
confidence: 71%
“…Mental retardation was a part of this variant and very few of the patients survived the first few weeks of life. 13 Our patient was three months of age and her postnatal mental and physical growth and development were normal. It was reported to be a sporadic case by the genetics department as there was no genetic abnormalities in her parents and relatives.…”
Section: Discussionmentioning
confidence: 71%
“…This uncommon disorder is considered to be autosomal dominant, though autosomal recessive inheritance has been suggested [10]. The most consistent malformations of this syndrome, in descending order of frequency, are the popliteal pterygium (webbing of the skin extending from the ischial tuberosities to the heels), cleft palate and/or lip, mostly an extensive single lower lip pit with salivary drainage, genital anomalies and synechia or syngnathia.…”
Section: Discussionmentioning
confidence: 99%
“…Kondo et al have demonstrated that mutations in the gene encoding of the transcription factor interferon regulatory factor 6 (IRF6) cause DVWS. The IRF6-protein, which plays a predominant role in embryological facial development, is found in the medial edges of the paired palatal shelves around the time of fusion [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, he did not present with pterygia, the cardinal feature present in the majority of cases of BPS [2, 6]. The case survived to adolescence although it is well known that the BPS is a lethal syndrome with very few case reports of patients who survived beyond infancy [3, 4]. The patient had mental retardation and short stature, two characteristics that were not argued in BPS due to early lethality of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Most affected cases die perinatally or few months after birth [2], although occasional survival has been reported [3, 4]. Since its first description in 1972 [1], BPS has been diagnosed repeatedly in literature with 24 cases reported up till now, mostly of Mediterranean ancestry [5, 6].…”
Section: Introductionmentioning
confidence: 99%